Assessment of serum zinc level in childhood malignancy at time of initiation of chemotherapy and to study its association with survival during initial first month of the treatment - Gautam, Arun; Verma, Nishant; Verma, Sonali (International Journal of Contemporary Pediatrics, 2022)
Background: Survival in childhood malignancies continues to be a challenge in developing than in developed countries. Multiple factors have been implicated for this gap, like poor health infrastructure, over-population and malnutrition. Malnutrition and associated zinc deficiency may be implicated as one preventable factor for mortality in childhood malignancy. The main aim of this study was to assess serum zinc level in childhood malignancy and to study its role in survival of the subjects. Methods: This prospective observational study was conducted from August 2014 to July 2015 on 219 patients of various childhood malignancies, from age 2 months to 15 years (151 males, 68 females). Cases were enrolled at the initiation of chemotherapy and followed for 1 month. Results: Serum zinc level (mean ± SD) was 78.70±32.83 µg/dl in the cases and it was found to be significantly lower than in controls (p<0.05). During follow up, 51 patients died due to various complications and disease progression. Significant relationship between low serum zinc level and unfavourable outcome was found (p<0.05). Logistic regression analysis revealed zinc level to be a significant predictor of the final outcome. Conclusions: This study states that low serum zinc level has an association with mortality in pediatric malignancy. As this study did not include any intervention in form of zinc supplementation, a future study with intervention of zinc supplementation might help in implicating the role of zinc as a predictor of outcome in childhood malignancy.